1997
DOI: 10.1128/jcm.35.5.1077-1079.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four different sampling methods for detecting pharyngeal carriage of Streptococcus pneumoniae and Haemophilus influenzae in children

Abstract: Samples from 96 children with acute respiratory infection were obtained simultaneously with nasal, nasopharyngeal, and oropharyngeal swabs and by nasopharyngeal aspiration and were cultured on chocolate and blood agar plates. The rates of isolation of Streptococcus pneumoniae and Haemophilus influenzae detected by the four sampling methods were compared. Nasopharyngeal aspirates were optimal for the detection of both S. pneumoniae (isolation rate, 33%) and H. influenzae (isolation rate, 31%). When a nasopharyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 14 publications
4
29
1
Order By: Relevance
“…In general, the detection rates differ for each respiratory virus but are especially high in RSV-infected patients [24]. The detection rates for common (Streptococcus pneumoniae and Haemophilus influenzae) and atypical bacterial pathogens (M. pneumoniae and C. pneumoniae) are comparable between NPA and nasal swab [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the detection rates differ for each respiratory virus but are especially high in RSV-infected patients [24]. The detection rates for common (Streptococcus pneumoniae and Haemophilus influenzae) and atypical bacterial pathogens (M. pneumoniae and C. pneumoniae) are comparable between NPA and nasal swab [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies comparing two sampling techniques suggest that the yield of both methods were similar for H. influenzae . 22,23 Crowding or number of siblings in a family was reported to increase Hib carriage rate. 19,24,25 The influence of concurrent upper respiratory symptoms on Hib carriage rates remains controversial, and studies differ in their findings on the influence of season, sex, tobacco exposure and race on carriage rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although obtaining a nasopharyngeal (NP) swab is minimally invasive, performance of multiple tests usually requires obtaining multiple specimens. Although some investigators have reported using nasal samples for multiple tests, (1)(2)(3)(4)(5) we are not aware of any studies that have used a single NP swab to evaluate viral, bacterial and host parameters.…”
Section: Introductionmentioning
confidence: 99%